Vloga in pomen zelenega prostora v novejših slovenskih stanovanjskih soseskah - Gazvoda, Davorin (Urbani izziv, 2001)
The design of new housing estates in Slovenia isn't improving despite new technologies and expansive professional knowledge in various fields from urbanand architectural design to landscape design of open spaces. Low availability of building space and desired growth of returns from given sites by increasing building density and quantity of homes are both diminishing possibilities for adequate design of green surfaces that could significantly improve the quality of the living environment. Comparison with older housing estates shows that green neighbourhood surfaces designed thirty or more years ago are much better. Despite changed social conditions, parameters defining high quality living environments haven't changed. Therefore at all levels of urban planning and aligned to adequate spatial policies it is necessary to strive for more spacious housing estates with larger shares of suitably designed green surfaces.
Keywords: bivalno okolje; mesta; mestne četrti; mestni predeli; parki; stanovanjske četrti; zelene površine; zelenice